Pelatihan Penggunaan Bahan Kimia untuk Cat Air Ramah Lingkungan - Arumsari, Alif Gita; Kusumawati, Desiana Nur Indra (Lembaga Publikasi Ilmiah Nusantara, 2025)
This paper explores the potential of natural chemical ingredients in the development of eco-friendly watercolor paints. Natural pigments derived from plants such as indigo, turmeric, and beetroot, combined with binders like gum arabic and egg yolk, offer promising alternatives to synthetic compounds. The study focuses on evaluating the color intensity, adhesion, drying time, and safety of these natural ingredients. The findings suggest that natural-based formulations can meet aesthetic and functional requirements while significantly reducing environmental impact. This supports a greener approach to art materials, aligning with sustainable and health-conscious innovation trends.